PENGARUH PEMBERIAN EKSTRAK KUNYIT (Curcuma longa linn) PADA LAJU PERTUMBUHAN BENIH IKAN NILA SALIN (Oreochromis niloticus) - Tasya Octaviani; Deni Sugianto; Indra Wirawan; Sumaryam Sumaryam (Universitas Mataram, 2026)
The purpose of this study was to determine which dose of turmeric (Curcuma longa linn) extract had the greatest impact on the growth rate of tilapia (Oreochromis niloticus) fry. The approach used was experimental, with direct observation used to collect data. Four levels of turmeric extract treatment were used in a completely randomized design (CRD): treatment (A) commercial feed (control), treatment (B) turmeric extract 20 ml/kg feed, treatment (C) turmeric extract 50 ml/kg feed, and treatment (D) turmeric extract 80 ml/kg feed. The results showed that the best treatment was treatment D (80 ml/kg feed) with an average specific growth rate of 19.83%. Water quality observations indicate that overall water quality remains at optimal levels to support the life of saline tilapia (Oreochromis niloticus) fry, with temperatures ranging from 27.2 to 31.1ºC, salinity ranging from 0.16 to 3.5 ppt, pH ranging from 4.7 to 8.63, and dissolved oxygen ranging from 9.4 to 15.08 mg/L.